Calidad de atención y fidelización del cliente en la banca negocio Scotiabank agencia Iquitos, 2022 - Guevara Garcia, Cissella Itzell (2023)
The thesis "Quality of service and customer loyalty in business banking Scotiabank agency Iquitos, 2022", has the general objective of determining the relationship between quality of service and customer loyalty in business banking of Scotiabank agency Iquitos, 2022. The study is of a descriptive - correlational type and of a non-experimental - cross-sectional design. The instrument used for data collection was the questionnaire, made up of questions organized with rating scales. The sample was taken in a simple random probabilistic way, with a total of 218 respondents. It was concluded that there is a relationship between the quality of s ervice and customer loyalty in the business banking of Scotiabank agency Iquitos, 2022. Keywords: values, organizational values, loyalty, customer loyalty.